Analysis of subjective signs in patients after secondary glaucoma surgeries - Juraj Sekac; Silvia Ferkova; Ivajlo Popov; Jela Valaskova; Robert Furda; Darina Lyskova; Paulina Plesnikova; Jan Rybar; Angelika Puzserova; Alena Furdová (Journal of Ophthalmology, 2023)
Purpose